PERUBAHAN POLA PENCITRAAN RIDWAN KAMIL DALAM PILWAKOT BANDUNG 2013 DAN PEMILIHAN GUBERNUR JAWA BARAT 2018 - Abie Besman; Meilanny Budiarti Santoso (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2017)
This study will analyze the changes of imagery on Twitter account @ridwankamil between the time of Pilwakot Bandung Campaign 2013 and pre-campaign West Java pre-campaign 2018, using discourse analysis of Teun Adrianus Van Dijk. This study aims to find the changes of image displaying by Ridwan Kamil on his Twitter with perspective of The strongmanship by Charles Manz and Henry Sims. The research method used is Discourse Analysis Model Van Dijk with qualitative paradigm - constructivism. Van Dijk Discourse Model mandated three steps of data collection and analysis on tweets that appear in the account @ridwankamil. First, the analysis found a textual construction by Ridwan Kamil to persuade tweet readers Discourse of social cognition showed Ridwan Kamil saw himself as a The Strongman who positioned to provide a solution to the problem of Bandung. Discourse of the social context shows Ridwan Kamil foundation of communication in the world of Twitter is to use an emotional approach to persuade and directed image of Ridwan Kamil. The researchers concluded the significance changes within most of the Tweets uploaded by this account campaign period is to use the image of Ridwan Kamil, at the Pilwakot campaign, Ridwan Kamil uses a Visionary Hero, but at the West Java pre-campaign, Ridwan Kamil uses the Strongmanship, to bring new way of relationship, using a trust and social responsibility to deflect a negative issue, such as religion and racism issue These results prove that Ridwan Kamil is a leader who can change his image, in social media effectively with an emotional approach to get the impression of the character more of a functional leader than structurally. Keywords: Ridwan Kamil; Campaign; Twitter; Discourse Analysis; Van Dijk; image